2022
DOI: 10.1007/s11010-022-04430-3
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte expressed chemerin-156 does not protect from experimental non-alcoholic steatohepatitis

Abstract: Non-alcoholic steatohepatitis (NASH) is a rapidly growing liver disease. The chemoattractant chemerin is abundant in hepatocytes, and hepatocyte expressed prochemerin protected from NASH. Prochemerin is inactive and different active isoforms have been described. Here, the effect of hepatocyte expressed muChem-156, a highly active murine chemerin isoform, was studied in the methionine–choline deficient dietary model of NASH. Mice overexpressing muChem-156 had higher hepatic chemerin protein. Serum chemerin leve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…We first examined the effect of bioactive recombinant human chemerin (huChem-157) (R&D Systems, 2324-CM-025) on ovarian cancer cell lines in standard adherent 2D culture conditions. To choose the concentrations for treatment, we considered a study reporting that 100 ng/mL of huChem-157 is equivalent to a concentration of 25 ng/mL chemerin using standard ELISA [ 44 ]. Thus, we used 100 and 400 ng/mL of huChem-157, being equivalent to 25 or 100 ng/mL serum chemerin, which represents the usual range from non-obese to obese patients in vivo [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first examined the effect of bioactive recombinant human chemerin (huChem-157) (R&D Systems, 2324-CM-025) on ovarian cancer cell lines in standard adherent 2D culture conditions. To choose the concentrations for treatment, we considered a study reporting that 100 ng/mL of huChem-157 is equivalent to a concentration of 25 ng/mL chemerin using standard ELISA [ 44 ]. Thus, we used 100 and 400 ng/mL of huChem-157, being equivalent to 25 or 100 ng/mL serum chemerin, which represents the usual range from non-obese to obese patients in vivo [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…All observed in vitro effects of chemerin were triggered only by the higher concentration of 400 ng/mL of recombinant huChem-157, which is equivalent to 100 ng/mL chemerin in human serum. Initially, concentrations of 100 and 400 ng/mL were chosen for our experiments considering a study reporting that 100 ng/mL of recombinant huChem-157 is equivalent to a concentration of 25 ng/mL chemerin using standard ELISA, thus being comparable to usual chemerin serum levels between 25 and 100 ng/mL [ 44 ]. However, a weakness of this study is that we did not compare the effect of 100 and 400 ng/mL Chem-157 in each experiment, because in the initial experiment we observed that only the higher concentration showed an effect in 2D cell culture.…”
Section: Discussionmentioning
confidence: 99%